CONTROL DESIGN ON A BILINEAR SYSTEM USING INPUT-OUTPUT LINEARIZATION AND BACKSTEPPING METHOD - Ahmadin
The design of nonlinear control systems is a very important issue in control theory. Until now, there is no generally accepted method in the design of nonlinear controls for stability and tracking of system outputs. Therefore, in general, restrictions are made for certain nonlinear classes. Bilinear systems are a simple class of nonlinear systems. So that in this dissertation the study is limited to certain bilinear classes. Non-minimum phase nonlinear systems are recognized as a major bottleneck in many control design problems. There have been many control designs for non-minimum phase nonlinear systems, including control designs based on the gradient descent method, modified steepest descent method, iterative learning control method, output redefinition method, and others. This dissertation designs control on a particular class of bilinear systems using input-output linearization and the bakstepping method. The design begins by constructing a theorem to state the bilinear system non-minimum phase, minimum, or weak minimum. In a minimum-phase bilinear system, the control design is carried out by like a linear system. Whereas in the non-minimum phase system, the control design is carried out using the backstepping method to determine the control variables so that the system becomes stable and can track the desired output. In addition, in this dissertation, the output is redefined so that the bilinear system minimum phase. From the research results, obtained several theorems from certain classes of bilinear systems which show that the bilinear system is in a non-minimum, minimum or weak minimum phase. Furthermore, the non-minimum phase system can be stabilized so that it can track the desired output using the backstepping method. In addition, obtained a theorem to state a minimum-phase bilinear system with a new output.